Flirting with fifty - Porter, Jane, 1964- (Jove, 2022)
"Paige Newsom is finally at a place in her life where she's comfortable. She loves her job as a college professor in Southern California, lives close enough to her mother to visit her regularly, and has three daughters who are flourishing in their own careers. Paige has no plans to upend her life again after her divorce eight years ago, but she's about to embark on a new adventure: co-teaching a course that includes a three-week international field study.Paige can think of a dozen reasons why she shouldn't go, one being a dazzling Australian biologist who will be teaching alongside her. Professor Jack King is charismatic, a world traveler, and more like Indiana Jones than Indiana Jones, all of which unsettles Paige, who prides herself on being immune to any man's charms. She isn't looking for love, and it turns out, neither is he. But as the two co-professors lead the rigorous program together, first on campus, then in beautiful Tanzania, their biggest challenge will be working closely together while resisting the undeniable chemistry they feel when they're with each other."--